نصانية النص الجاهلي: القصائد الواحدة أنموذجا - الحراحشة، أحمد محمد مشرف (جامعة محمد بوضياف المسيلة - كلية الآداب واللغات, 2023)
من الجلي الواضح أن الدلالات المأنوسة المتوارثة لم تعد قادرة على إقامة صلب معاني البنية العميقة للشعر القديم خاصة، التي تفرضها المعطيات المتعالقة مع النص، مثل: مقام القصيدة وأحوال المقام، ودوافعه المرتبطة بموضوعها الرئيس، وسياقات البنية الداخلية والخارجية للنص التي لا تنفك تلتمع من تحت جمر الألفاظ بين لفظة وأخرى؛ لذلك يممت صوب النقد الغربي، ولحبت الطريق بمجمل أراء النقاد الغربيين؛ أمثال دي بوجراند ودرسلر وفندايك وهاليدي ورقية حسن وبراون ويول، ورولان بارت وغيرهم، ودرست تعريفاتهم للنص والمقام والسياق الاجتماعي والتاريخي، وحاولت تطبيق مناهجهم على النص الجاهلي فخرجت بنتائج افترقت فيها عن كل الدراسات السابقة والمعاصرة، وفي ظني أنني اقتربت كثيرا إلى معاني الشعر العربي الجاهلي وحقيقته في بيئته الأصلية صحراء الجزيرة العربية ومواضعات الحياة الجاهلية فيها. It is clearly evident that the inherited, nuanced connotations are no longer capable of establishing the core meaning of the deep structure of ancient poetry, especially those imposed by the interrelated factors with the text, such as the poem's context, its circumstances, the motivations related to its main subject, and the internal and external structural contexts of the text that constantly shine beneath the embers of words, from one phrase to another. Therefore, Western frameworks were adapted for the data analysis, and I followed the path of Western critics, such as De Bujrund, Dressler, Van Dijk, Halliday, Raghia Hassan, Brown, Yule, Roland Barthes, and others. I studied their definitions of text, context, and the sociohistorical factors, and attempted to apply their methods to pre-Islamic poetry, which led me to results that diverged from all previous and contemporary studies. In my opinion, I came much closer to the meanings of pre- Islamic Arabic poetry and its true nature in its original environment, the Arabian Peninsula's desert and the peculiarities of life in its pre-Islamic era.
Keywords: النص الجاهلي -- البنية العميقة -- الشعر القديم -- صحراء الجزيرة العربية